2018
DOI: 10.3389/fmicb.2018.01973
|View full text |Cite
|
Sign up to set email alerts
|

Viability RT-qPCR to Distinguish Between HEV and HAV With Intact and Altered Capsids

Abstract: The hepatitis E virus (HEV) is an emerging pathogen showing a considerable increase in the number of reported cases in Europe mainly related to the ingestion of contaminated food. As with other relevant viral foodborne pathogens, real-time reverse transcriptase polymerase chain reaction (RT-qPCR) is the gold standard for HEV detection in clinical, food, and environmental samples, but these procedures cannot discriminate between inactivated and potentially infectious viruses. Thus, the aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 50 publications
(81 reference statements)
3
42
1
1
Order By: Relevance
“…to report the presence of intact viral particles post treatment (Randazzo et al, 2018). The inactivation by HPP of other foodborne viruses, including norovirus, hepatitis A virus (HAV), and surrogates for foodborne viruses has been investigated (Kingsley et al, 2002;Kingsley, 2013;Lou et al, 2015;Lou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to report the presence of intact viral particles post treatment (Randazzo et al, 2018). The inactivation by HPP of other foodborne viruses, including norovirus, hepatitis A virus (HAV), and surrogates for foodborne viruses has been investigated (Kingsley et al, 2002;Kingsley, 2013;Lou et al, 2015;Lou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that replication of virus occurred, and therefore the elimination of HEV infectivity was not complete. In another study, it was shown that the treatment of HEV solution at 500 MPa for 15 min did not result in complete inactivation assayed by using viability markers (PMAxx and platinum chloride, PtCl4-RT-qPCR) (Randazzo et al, 2018). Knowing that the virus is capable of replication (and therefore has the potential to cause illness) is important for interpretation of surveillance and inactivation studies on HEV to inform risk assessment and mitigation (Cook et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first published study to quantify the inactivation of HEV following HPP treatment. HEV response to 500 MPa for 15 min has been previously investigated with RT-qPCR viability markers (PMAxx and platinum chloride, PtCl4-RT-qPCR), but was only able to report the presence of intact viral particles post treatment (43). The inactivation by HPP of other foodborne viruses, including norovirus, Hepatitis A virus (HAV), and surrogates for foodborne viruses has been investigated (26, 44-46).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that replication of virus occurred, and therefore the elimination of HEV infectivity was not complete. In another study, it was shown that the treatment of HEV solution at 500 MPa for 15 min did not result in complete inactivation assayed by using viability markers (PMAxx and platinum chloride, PtCl4-RT-qPCR) (43). Knowing that the virus is capable of replication (and therefore has the potential to cause illness) is important for interpretation of surveillance and inactivation studies on HEV to inform risk assessment and mitigation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Viability RT-qPCR assays have been used to estimate infectious HAV exposed to thermal treatments. The have been optimized in viral suspensions, tested in inoculated food concentrates (including lettuce, spinach, parsley, cockles, coquina clams, mussels, oysters and berries) and successfully applied in naturally contaminated river, sewage and reclaimed waters (Moreno et al 2015;Fuster et al 2016;Randazzo et al 2018bRandazzo et al , 2018cChen et al 2020) (Table 3).…”
Section: Assessing Hav Infectivity In Foodmentioning
confidence: 99%